The Term Structure of LIBOR Sterling Rates - Miłobędzki, Paweł (Struktura terminowa stóp LIBOR dla funta brytyjskiego, 2010)
A three-variable VAR including the yield spread, the change in the short rate and the excess holding period yield is used to test for the validity of rational expectations hypothesis of the LIBOR sterling rates term structure. In doing so the monthly series of one, three, six and twelve month LIBORs from the period January 1978 - June 2009 are utilized, all supplied by the Bank of England. The main findings from the analysis include these that for all maturities considered the yield spread Granger causes future changes in the one month rate, the term premia are not time-varying, and variation in the unexpected returns is due to news about the future one month rates and not due to news about the future term premia.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s. 88-102
Keywords: term structure of interest rates; rational expectations hypothesis; time varying term premium; London Interbank Market; VAR